Implementation of Guidance and Counseling Services for Early Childhood in KB As-Sholihin - Nur Aliyah; Yulianty, Nadya (Kiddie: Early Childhood Education and Care Journal, 2026)
In carrying out Early Childhood Education, it is necessary to provide guidance and counseling services as an effort to shape behavior in the process of adapting children to a social environment so that they can develop their potential and interests. The aim of this research is to find out empirical evidence regarding the implementation of Guidance and Counseling services at the As-Sholihin KB. The research method used was descriptive qualitative which was carried out at KB As-Sholihin Purwakarta. The research subjects were students aged 4-5 years and KOBER teachers. The data collection methods used were interviews, observation and documentation. The research results obtained from the implementation of counseling guidance services at the As-Sholihin KB consist of several strategies including: through educational game activities, art activities, role playing activities, group direction and sensory motor activities. The implementation of guidance and counseling services through several of the strategies above shows positive results for early childhood development at As-Sholihin KB.